Expression of the Mxra8 Receptor Promotes Alphavirus Infection and Pathogenesis in Mice and Drosophila - Zhang, Rong (Cell Rep, 2019)
Mxra8 is a recently described receptor for multiple alphaviruses, including Chikungunya (CHIKV), Mayaro (MAYV), Ross River (RRV), and O’nyong nyong (ONNV) viruses. To determine its role in pathogenesis, we generated mice with mutant Mxra8 alleles: an 8-nucleotide deletion that produces a truncated, soluble form (Mxra8(Δ8/Δ8)) and a 97-nucleotide deletion that abolishes Mxra8 expression (Mxra8(Δ97/Δ97)). Mxra8(Δ8/Δ8) and Mxra8(Δ97/Δ97) fibroblasts show reduced CHIKV infection in culture, and Mxra8(Δ8/Δ8) and Mxra8(Δ97/Δ97) mice have decreased infection of musculoskeletal tissues with CHIKV, MAYV, RRV, or ONNV. Less foot swelling is observed in CHIKV-infected Mxra8 mutant mice, which correlated with fewer infiltrating neutrophils and cytokines. A recombinant E2-D71A CHIKV with diminished binding to Mxra8 is attenuated in vivo in wild-type mice. Ectopic Mxra8 expression is sufficient to enhance CHIKV infection and lethality in transgenic flies. These studies establish a role for Mxra8 in the pathogenesis of multiple alphaviruses and suggest that targeting this protein may mitigate diseasein humans.